2014
DOI: 10.1039/c4nr02791d
|View full text |Cite
|
Sign up to set email alerts
|

Generic phosphatase activity detection using zinc mediated aggregation modulation of polypeptide-modified gold nanoparticles

Abstract: A generic plasmonic assay for rapid detection and characterization of a wide range of phosphatases using different natural substrates is described that exploit the enzymatic release of inorganic phosphate to control the aggregation of nanoparticles functionalized with a designed Zn2+responsive polypeptide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Gold nanoparticles (AuNPs) (20 nm, Cline Scientific AB) were functionalized with the peptide JR2EC as described previously 32 , 36 .…”
Section: Methodsmentioning
confidence: 99%
“…Gold nanoparticles (AuNPs) (20 nm, Cline Scientific AB) were functionalized with the peptide JR2EC as described previously 32 , 36 .…”
Section: Methodsmentioning
confidence: 99%
“…[23][24][25][26] Literature survey revealed that very few colorimetric methods for the detection of Al 3+ and Zn 2+ are reported using surface functionalized AuNPs, in compared to other metal ions such as Hg 2+ , Cu 2+ , Pb 2+ etc. [27][28][29][30][31][32][33][34][35] Also, the nanoprobes have been recently applied for the construction of Boolean logic gates, which are promising in the fabrication of molecular computation and becoming a potential substitute for the traditional silicon-based computation. [36][37][38][39][40][41] Continuing our research on the chemosensors development with vitamin B 6 cofactors like pyridoxal (PL), pyridoxal 5-phosphate (PLP), [42][43][44] herein, we have developed a rapid colorimetric nanoprobe with good selectivity for Al 3+ and Zn 2+ using an organic ligand functionalized AuNPs.…”
Section: Introductionmentioning
confidence: 99%
“…JR2EC, JR2E and D-Ala-JR2EC (peptide identity and sequences in Supporting Information) were synthesized using Fmoc-strategy and sequentially purified as described 4 previously. 26 Linking two peptides via a disulfide bridge was carried out by dissolving peptides (2 mg/ml) in ammonium hydrogen carbonate buffer (10 mM, pH 8.5), and subsequent incubation for 72 hours at room temperature on an orbital-shaker. Formation of the disulfide bridge was confirmed by an Ellman's test of free thiols.…”
Section: Methodsmentioning
confidence: 99%
“…JR2EC functionalized AuNPs (40 nm in radius) were synthesized as described previously. 26 AuNPs ~70 nM (BBI Solutions, UK) were incubated with 10 µM JR2EC (10 mM sodium citrate, pH 6) at 4 °C overnight. After incubation the particles were repeatedly centrifuged (12,000 × g, 30 min) and the buffer subsequently exchanged with Bis-Tris buffer (30 mM, pH 7) until the concentration of unbound JR2EC was below 5 pM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation